SmallWorld: A Test and Training System for the Cyber-Security - Angelo Furfaro; Antonio Piccolo; Domenico Saccà (European Scientific Journal, ESJ, 2016)
Powerful malware infects millions of computers every day and data breaches continue to increase. Cyber-Security incidents grow in frequency, the costs of managing and mitigating breaches also are rising. This situation demands for a suitable number of information security specialists to adequately handling issues arising in such a complex domain. This paper describes SmallWorld, a scalable software platform designed to reproduce realistic scenarios achieved by the immersion of real systems into a virtual environment with a fully integrated support for teaching with the aim to provide a venue for practical education in the learning and usage of all tools, techniques, and best practices employed to protect the confidentiality, integrity, authenticity, and availability of a designated information service. This software can be successfully adopted during high school, university and specific training to improve the quality and the results of the courses.